Kajian Erosi pada Hutan Tanaman Industri di Kecamatan Tompobulu Kabupaten Maros: Erosion Study in Industrial Plantation Forests in Tompobulu District, Maros Regency - Lias, Syamsul Arifin; Laban, Sartika; Asyraf, Muhammad (Universitas Hasanuddin, 2023)
The small value of erosion on a land is sometimes ignored even though it can sometimes have an effect on a land. Industrial plantation forests (HTI) are present as a government effort to combine timber production and forest rehabilitation. However, the problems faced are low land productivity, decreased soil fertility due to erosion processes in the soil layer. The research hypothesis is that the use of a layered canopy, good soil infiltration will reduce the rate of erosion and surface flow. This research aims to study the amount of erosion in industrial plantation forests in Tompobulu District, Maros Regency. This research was conducted in January-February 2022 in Bahagia Hamlet, Bontomanurung Village, Tompobulu District which was carried out using the erosion plot method. Erosion plots were made in two stands in monoculture and agroforestry industrial plantation forest areas. The measurement results of the amount of flow rate in monoculture HTI is greater than agroforestry HTI which each has a surface flow, namely 113.86 m3/ha and 55.43 m3/ha. While the erosion rate in monoculture HTI is greater than agroforestry HTI, each of which has an erosion rate, namely in monoculture HTI of 0.19 tons/ha and agroforestry HTI of 0.06 tons/ha. The estimated value of annual erosion and tolerable soil loss (TSL) in each stand, namely monoculture HTI is 2.57 tons/ha/year and 4.69 tons/ha /year, while in agroforestry HTI respectively 1.45 tons/ha/year and 9.69 tons/ha/year. Each of the two stands produced estimates of annual erosion that were smaller than the tolerable soil loss (TSL). Good interception (use of layered canopy, vegetation with large leaf surface area) and good infiltration can reduce erosion and surface runoff.